PENGARUH PROFITABILITAS, LEVERAGE, CORPORATE SOCIAL RESPONSIBILITY, DAN KEPEMILIKAN ASING TERHADAP EFFECTIVE TAX RATE (STUDI KASUS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016—2019) - Martin, Danny (Jurnal Ilmiah Mahasiswa FEB, 2020)
According to Tax Directorate General, Indonesia’s tax ratio even now ranges from 10 to 14 %, allegedly due to the tax avoidance cases, in which Panama Papers is the most significant finding. Tax Justice Network and Publish What You Pay Indonesia reveal intercompany transactions among mining companies as one of the forms of tax avoidance. This study aims to examine the effect of profitability, leverage, corporate social responsibility (CSR), and foreign ownership on effective tax rate. This research applies quantitative approach with causal study, and utilizes secondary data. 48 mining companies listed on Indonesia Stock Exchange between 2016—2019 are the samples selected through purposive sampling method. The data analysis indicates that profitability, leverage, CSR, and foreign ownership have a simultaneous effect on effective tax rate. Partially, profitability has a negative effect on effective tax rate, and CSR has a positive effect on effective tax rate. Whilst, leverage and foreign ownership have no effect on tax avoidance.Keywords: Effective tax rate, tax avoidance, profitability, leverage, corporate social responsibility (CSR), foreign ownership